Characterization of floating microplastic contamination in the bay of Marseille (French Mediterranean Sea) and its impact on zooplankton and mussels. (February 2022) - Gérigny, O.; Pedrotti, M.-L.; El Rakwe, M.; Brun, M.; Pavec, M.; Henry, M.; Mazeas, F.; Maury, J.; Garreau, P.; Galgani, F.
Abstract: Microplastics (MPs) were sampled in three seasons from 2016 to 2018 in the Bay of Marseille, northwestern Mediterranean Sea, adjacent to a highly urbanized area. Six sites were selected according to their different characteristics (river mouth, treatment plants, protected marine area). Surface floating MPs were characterized (number, weight, typology and polymer) as was zooplankton. In addition, mussels were submerged and used to investigate ingestion. Finally, a hydrodynamic model was used to improve understanding of dispersion mechanisms. The annual averages of floating MPs values ranged from 39, 217 to 514, 817 items/km 2 . The MPs collected were mainly fragments principally composed of polyethylene and polypropylene. The mean abundance ratio (MPs/zooplankton) was 0.09. On average 87% of mussel pools were contaminated and ingested 18.73 items/100 g of flesh. Two hydrodynamic patterns were identified: the first retaining the MPs in the harbor, and the second dispersing them outside. Highlights: The distribution and fate of microplastics were evaluated in the bay of Marseille (French Northwestern Mediterranean Sea). The floating MP reached more than 3.6 million items·km 2, mainly composed of polyethylene and polypropylene. 87% of mussels ingested microplastics, with concentrations at 18.73 items/100 g of tissues on the average. The ratio microplastics/zooplankton is a potential indicators of interactions between microparticles and zooplankton. Two hydrodynamic patterns were identified through modelling studies, including retention in harbor and dispersion offshore.